Gout Activity Score has predictive validity and is sensitive to change: results from the Nottingham Gout Treatment Trial (Phase II). (4th February 2019) - Chinchilla, Sandra P; Doherty, Michael; Abhishek, Abhishek
Abstract: Objectives: To examine the predictive validity of the Gout Activity Score (GAS), its correlation with the Gout Impact Scale (GIS) and their sensitivity to change. Methods: Data from a clinical trial in which participants with one or more gout flares in the previous year were recruited from primary care and randomized to nurse-led or continuing usual care were used in this study. GAS and GIS were calculated as described, with higher scores indicating worse disease activity and quality of life, respectively. The correlation between GAS and GIS was examined using Spearman's correlation. Standardized response means (SRMs) were calculated to assess sensitivity to change. The association between GAS at baseline and the number of flares in the next 12 months was evaluated using Poisson regression. Data analyses were performed using STATA version 14, with P -values <0.05 being statistically significant. Results: There was low positive correlation between GAS and gout concern overall and unmet treatment need subscales of GIS ( r = 0.34–0.45). Female sex associated independently with fewer gout flares, while increasing GAS, BMI and age associated independently with frequent flares. Of all the outcome measures examined, GAS was the most responsive to change (SRM 0.89 to −0.53). Of the GIS domains, the gout concern overall domain had the best sensitivity to change (SRM 1.06–0.01). Conclusion: GAS is sensitive to change, has predictive validity and correlates with relevant domains of GIS such as gout concern overall. Additional independent validation of GAS is required before it can be adopted in clinical practice.